Novos paradigmas do ensino de literatura no Brasil : as publicações da década de 1980 - Dutra, Aylon de Oliveira (2023)
This research has as its theme the change in the paradigm of literature teaching in Brazil from the content analysis of works on the subject published during the 1980s. Thus, its general objective is to analyze such works, verifying their contributions to this change. In addition, with regard to specific objectives, we also sought to systematize the discussions held during the period; identifying the causes for an increase of interest in the subject in Brazil during that decade, contextualizing it historically; and how the selected works approach the contemporary paradigms and which criticisms point to the traditional paradigms of literature teaching. For this, seven works were selected that address the issue of teaching literature in secondary education. As for the theoretical foundation, we follow the budgets of Cosson (2020, 2018) and Paulino and Cosson (2009) regarding the notion of paradigms of literature teaching; on the history of literature teaching and education in Brazil, Azevedo (1944, 1999), Cardoso (2016), Cereja (2005), Leite (1983), Razzini (2000), Ribeiro (1992) and Souza (1999); with regard to different theoretical currents related to reading, Jouve (2002), Kleiman (2002, 2016), Soares (2020) and Zilberman (1989). Regarding its nature, it is an applied research; as for its objectives, it constitutes an exploratory research; in relation to technical procedures, the research is bibliographical and documental; and as for the approach, it will be qualitative and quantitative. In this way, the corpus was subjected to data analysis and interpretation according to the Content Analysis methodology (BARDIN, 2016). The corpus analysis was carried out based on two sets of categories: the first reference to the content of the works, which revealed a greater interest in socio-historical issues; and the second referring to the literature teaching paradigms, which revealed a closer relationship with the Reader's Education paradigm. We therefore conclude that, from the 1980s onwards, there was the beginning of a gradual process of paradigm shift in literature teaching in Brazil.